تأثير التعليم التحضيري في مستوى الاستعداد القرائي لتلاميذ سنة الأولى ابتدائي دراسة ميدانية ببعض ابتدائيات سيدي عيسى - ميزي سهيلة; براح سميحة; اشراف: عزوق جميلة (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة الحالية إلى التعرف على تأثير التعليم التحضيري في مستوى الاستعداد القرائي لتلاميذ سنة الأولى ابتدائي. وبغية التحقق من فرضيات البحث تم اعتماد المنهج الوصفي من خلال تطبيق استبيان الاستعداد القرائي على عينة من أساتذة التعليم الابدائي ببلدية سيدي عيسى، حيث تكونت عينة الدراسة من 50 أستاذ وأستاذة. توصلت الدراسة الحالية إلى النتائج التالية: يوجد أثر ذو دلالة إحصائية للتعليم التحضيري في مستوى الاستعداد القرائي لتلاميذ السنة أولى ابتدائي. يوجد أثر ذو دلالة إحصائية للتعليم التحضيري في تنمية مفردات اللغوية لتلاميذ السنة أولى ابتدائي. يوجد أثر ذو دلالة إحصائية للتعليم التحضيري في تنمية مهارات التمييز السمعي لتلاميذ السنة أولى ابتدائي. يوجد أثر ذو دلالة إحصائية للتعليم التحضيري في تنمية مهارات التمييز البصري لتلاميذ السنة أولى ابتدائي. الكلمات المفتاحية:الاستعداد القرائي، التعليم التحضيري، المفردات اللغوية، التمييز السمعي، التمييز البصري. Abstract: The current study aimed to identify the impact of preparatory education on the level of reading readiness of First-Year Primary School students. In order to verify the research hypotheses, the descriptive curriculum was adopted by applying the reading readiness questionnaire to a sample of primary education teachers in the municipality of Sidi Issa, where the study sample consisted of 50 professors and professors. The current study came to the following conclusions: - There is a statistically significant effect of preparatory education on the level of reading readiness of pupils of the first year of primary school. - There is a statistically significant impact of preparatory education on the development of vocabulary for pupils of the first year of primary school. - There is a statistically significant impact of preparatory education on the development of auditory discrimination skills of first-year primary pupils. - There is a statistically significant impact of preparatory education on the development of visual discrimination skills for first-year primary students. Keywords: reading readiness, preparatory education, vocabulary, auditory discrimination, visual discrimination.